Caracterizando mi ciudad- curso virtual en la plataforma Easy Lms para el aprendizaje del español como lengua extranjera a través de la cultura bogotana. - Polanco Hernandez, Natalia (Universidad Antonio Nariño, 2021)
The Spanish language as a foreign language is gaining strength worldwide. That is why the proposal “Caracterizando mi ciudad, curso virtual en la plataforma Easy LMS para el aprendizaje del Español como Lengua Extranjera a través de la cultura bogotana” has been designed with the purpose of developing foreign communication skills in a context of cultural immersion. For this, a digital platform is proposed that comprises a course structured in four modules. Each one frames the most relevant aspects of Bogota culture, such as gastronomy, transport, typical food, emblematic places and tallest buildings, among others. These cultural traits are articulated with the use of popular expressions typical of the Bogota context. Therefore, it is expected to contribute to the development of the communicative competence of foreigners in a simple and natural way, fostering spaces for immersion in culture through an interactive digital course.